Clinico-Pathological Profiles and Outcomes of Acute Viral Encephalitis in Children (Bangladesh Journal of Infectious Diseases, 2020)
Background: Encephalitis is an acute inflammatory process that affects brain tissue and is almost always accompanied by inflammation of the adjacent meninges. The disease is most commonly caused by viral infection.Objective: The purpose of the present study was to determine the clinical and cerebrospinal fluid profile of childhood encephalitis and to document Herpes simplex antibody status in cerebrospinal fluid.Methodology: This descriptive analytical study was conducted in Department of Paediatrics of Shaheed Suhrawardy Medical College Hospital and Dhaka Medical College Hospital from May 2011 to October 2011. A total of 30 children of encephalitis were included in this study. Cerebrospinal fluid (CSF) routine and Herpes Simplex virus (HSV) antibody in CSF were done to all patient.Result: Fever and convulsion was found in 29(96.7%) and 28(93.3%) cases respectively in studied patients. Altered level of consciousness was present in 29(96.7%) cases. Fever, convulsion and altered level of consciousness was statistically significant (p